The contribution of different public innovation funding programs to SMEs' export performance - Rebecca Liu; Christian Rammer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
This paper studies the effects of different public innovation funding programs on the innovation output and export performance of small and medium-sized enterprises (SMEs). We evaluate the effectiveness of regional, national and European funding programs implemented in Germany for both product and process innovations. Our panel study shows that public financial support contributes to higher innovation outputs, which in turn translates into higher export success in later years. This relation however only holds for certain sources of public funding and certain types of innovation output. Innovation support from the European Union and national programs for cutting-edge technology that results in higher sales with new-to-market products shows a significant positive effect on SMEs' export performance. For funding programs run by regional authorities, we find similar though relatively smaller impacts on both innovation output and exporting. Bottom-up funding at the national level-which allows firms to freely define the design of the funded innovation projects in terms of content and cooperation-increases sales with innovations that are only new to the firm, but these innovations have limited impacts on export success. Our results suggest that public innovation programs should challenge SMEs to go for more ambitious innovations in order to strengthen their competitiveness.
urn:nbn:de:bsz:180-madoc-415917
Keywords: O32; O38; F14; 330; Public Funding; SMEs; Innovation Outputs; Exporting; Panel Study; Matching